Body Image and Self-Confidence in Young Women Who are Victims of Body Shaming - Annisaa Regina Kencana Putri; Made Padma Dewi Bajirani (Philanthropy: Journal of Psychology, 2024)
Abstract. The act of body shaming makes young women feel sad and insecure. Young women need high self-confidence to be able to support their developmental tasks. One of the factors that supports increasing self-confidence is an assessment of physical appearance or body image. This research aims to explore the correlation between body image and self-confidence among young women who have been victims of body shaming, utilizing a correlational quantitative approach. The respondents in this study were 170 teenage girls aged 12 to 15 who were victims of body shaming in Denpasar City. Data collection involved administering validated and reliable self-confidence and body image scales. The findings revealed a significant relationship between aspects of body image (appearance evaluation, appearance orientation, body area satisfaction, overweight occupation, and self-classified weight) and self-confidence among young women who were victims of body shaming (p=0.000 < .05). This study underscores the critical need for interventions and support systems to address body shaming among young women, emphasizing the importance of fostering positive body image to enhance self-confidence and well-being.Keywords: body image; self-confidence; body shaming